Managerial Incentives and Financial Contagion - Chakravorti, Sujit (IMF Working Papers; Working Paper ;, 2004)
This paper proposes a framework for comovements of asset prices with seemingly unrelated fundamentals, as an outcome of optimal portfolio strategies by fund managers. In emerging markets, dedicated managers outperforming a benchmark index and global managers maximizing absolute returns lead to systematic interactions between asset prices, without asymmetric information. The model determines optimal portfolio weights, the incidence of relative value strategies, and the systematic deviation of prices from fundamentals with limits to arbitraging this differential. Managerial compensation contracts, optimal at the firm level, may lead to inefficiencies at the macroeconomic level. Conditions are identified when shocks in one emerging market affect others.